The comparative influence of traditional celebrities and digital influencers in fashion industry for generation z - Lai, Pei Xuan (2025)
This study explores how traditional celebrities, and digital influencers affect Generation Z’s purchasing intention in the fashion industry. Using the Source Credibility Theory and Information Acceptance Model, it examines the impact of expertise, attractiveness, trustworthiness, engagement level, and information quality on Generation Z’s purchasing intention influenced by endorsers. A total of 392 gen Z participants were surveyed using convenience and snowball sampling through Google Form. The research aims to identify the key factors influencing Gen Z’s purchasing intention and offer insights for marketers to create more effective, targeted strategies. It contributes to existing literature by comparing influencer types and their roles in modern fashion marketing.